If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6ax = 0 Reorder the terms: 6ax + 3x = 0 Solving 6ax + 3x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3x' to each side of the equation. 6ax + 3x + -3x = 0 + -3x Combine like terms: 3x + -3x = 0 6ax + 0 = 0 + -3x 6ax = 0 + -3x Remove the zero: 6ax = -3x Divide each side by '6x'. a = -0.5 Simplifying a = -0.5
| 5/4y=12 | | 5(2m+7)-m= | | 4x^5y^4+12x^2y^3-16xy^5=0 | | 6x-7=12x+29 | | 8(x+6)+6(x+6)=6x-6 | | x+3+5x-8= | | 2x*(x+5)=0 | | 2y^4(4y+1)(y-2)=0 | | -1/2x-3=-1/2x-10 | | 2x^2+4x*sqrt(1-x^2)-1=0 | | (x-9)+(2x+29)+(x)=180 | | 5(2z-4)=8(z+3) | | 8x+9=13x-6 | | 5y^4(3y^2-12y)(y-4)= | | (-1)-(-9)= | | 3b=9-a | | 10x+1=2x+57 | | 1/2x-3=1/2x-10 | | p-8=5p | | 5l+5w=42 | | X+25+X+30=180 | | 2x+2y=2000 | | 5y=8(5y-7) | | 1/2x-10=1/2x-3 | | 2x(3x-4)=2x(3x+8) | | 21-y=26 | | 14+0.3333x=40 | | 3x/7=2/7=2 | | 0.1=cos(x) | | 7/4-7/3 | | 8n^2-10n-3=0 | | 5/3-4 |